URGENSI PENCANTUMAN HAK-HAK ISTRI DALAM GUGATAN CERAI DI PENGADILAN AGAMA KELAS I-A PONTIANAK - Febriani, Sabila; Ma'u, Dahlia Haliah; Muzammil, Sa’dulloh (Al-Usroh, 2024)
The purpose of this research are to know: 1) Why did the inclusion of wives’ rights come as a requisite for filing a divorce at the religion court of the I-A Pontianak; 2) the effect of filing wives’ rights in filing for divorce at the religion court of the I-A Pontianak. Researchers use qualitative methods of study with a type of empirical judicial research and a qualitative approach. Data sources use the primary data of the religious court judge as a source in interviews conducted by researchers. While secondary data sources include a compilation of Islamic law, SEMA, PERMA, a letter from the Dirjen Badilag of the republic of Indonesia, books, journals, articles, and so forth on the research topic. A data-collection technique that conducting interviews and accompanied by documentation. Then technical data analysis, researchers performed data reduction, data presentation and came up with a conclusion. Then, the data was verified by the member check. The result of this study show that: 1) The inclusion of wives’ rights as a requisite for filing a divorce isn’t a requirement for filing a divorce at the religious court of the I-A Pontianak. But, the inclusion of women’s rights after divorce is highly recommended, because it has a rule over such rights, which is the rights of the post-female population of iddah living, of mut’ah and madhiyyah; 2) The positive effect of these regulations is to provide protection for women’s rights after divorce and to give their wives an advantage in post-divorce finance, while the negative effects of the divorce lawsuit that the wife makes are even higher than the husband’s. The effect of women’s rights after the divorce also affects the level of legal compliance, and the effect on the divorce proceedings is that it can make the trial long to the point of proof.